Future international manager: Employers's perceptions on the performance of BIBM practicum students - Mansor, Mohd. Najib (Universiti Utara Malaysia, 2007)
The increase in the number of graduates from higher institutions and their inability to secure jobs after graduating would pose serious problems to national development programs.Most of these fresh graduates are new to the working environment and are facing ‘culture shock’ when entering an organization.Universiti Utara Malaysia has taken a very important step by offering a practicum training program to final year students and exposed them to the working environment.These experiences that the students gain would reduce ‘the shock’ that they will be facing in the working world.For this purpose, the focus of this research is to address two important issues.First, whether Bachelor of International Business Management (BIBM) students perform well in their practicum training, and second, do these students meet the skills requirements needed by the organizations? The findings revealed that BIBM students did perform well in their practicum training especially those students doing their practicum at public organizations.Even though there were no significant differences in the performance between male and female students, the study did reveal that students performed better at public institutions rather than at private institutions.Chinese students were well ahead of the other students as they were more punctual.Lastly, BIBM students showed that they have the quality and skills that would bring them closer in becoming international managers in the future.